2021
DOI: 10.1093/ahr/rhab359
|View full text |Cite
|
Sign up to set email alerts
|

Critical Digital Archives: A Review from Archival Studies

Abstract: Given the blurring of boundaries between historians and archivists in the digital realm, this article urges historians to pay more attention to discussions surrounding digital records and archival practices emerging from critical archival studies. More specifically, this article identifies and summarizes seven key themes and corresponding debates about digital records in contemporary archival studies scholarship: (1) materiality, (2) appraisal, (3) context, (4) use, (5) scale, (6) relationships, and (7) sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Researchers from the United States analyzed the use of online archives and libraries in the process of studying history and concluded that the level of motivation of students to learn under the influence of modern digital technologies (Carbajal and Caswell, 2021). The advantages of using online libraries and online archives, as in our study, identified ease of use, visualization of historical events and historical figures, digitized documents of different historical periods and maps, movies and videos on historical events and others.…”
Section: Discussionmentioning
confidence: 74%
“…Researchers from the United States analyzed the use of online archives and libraries in the process of studying history and concluded that the level of motivation of students to learn under the influence of modern digital technologies (Carbajal and Caswell, 2021). The advantages of using online libraries and online archives, as in our study, identified ease of use, visualization of historical events and historical figures, digitized documents of different historical periods and maps, movies and videos on historical events and others.…”
Section: Discussionmentioning
confidence: 74%
“…Being aware of why the archival document is described and presented the way it is by the archival organisation can help expert users to usefully question the archival organisation's descriptions around it in light of various drivers such as the organisation's purpose (we are created to collect these things), aims (we hope to achieve these things), resources (we have the money to do these things), personnel (we have these people to do these things), underlying methodology (we do things this way), and prescribed audience (we do things for these groups of people). Combined with an awareness of intended purpose, an expert user can better understand the fullness of the collection in which the archival document sits and the archival organisation's own custodial approach, helping them to determine aspects such as who 'owns' the archival document, whether it has a full description or is 'divorced' from the context of its creation, 46 whether there is a 'misleading impression of completeness' 47 or it exists as part of an 'archival diaspora' divided across institutions. 48 The different services around the acquisition and management of the archival document (notably, transfer/donation, selection/appraisal, arrangement and description) can also be reviewed through the lens of articulated purpose.…”
Section: Articulated Purposementioning
confidence: 99%
“…For instance, by being aware that when reading through lists of selected holdings that often much more was destroyed than kept, and that 'all archival collections are compendia of silences'. 96 Purpose knowledge can therefore aid understanding of the connection or disconnection between the archival document and its intended and actual purposes.…”
Section: Purpose Knowledge Helps To Assist With Identifying the Valid...mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Digital archives systematically describe digital resources so that users can effectively search and view the materials. 7 In general, digital archives describe digital resources based on guidelines for expressing standard metadata elements and data values that are mainly used in the domain. For example, the US Library of Congress is creating digital resources with varying levels and types of descriptive metadata, providing an increasingly coordinated and standardized approach to the creation and management of descriptive metadata.…”
Section: Introductionmentioning
confidence: 99%